2013
DOI: 10.1080/01496395.2013.808669
|View full text |Cite
|
Sign up to set email alerts
|

High Selective Separation of Flavonoids based on Crosslinked Chitosan Resin Grafted by Quercetin

Abstract: In this study, crosslinked chitosan resin grafted by quercetin (QCCR) was used as a novel adsorbent to separate flavonoids. Functional quercetin groups were introduced to the adsorbent matrix, and the hydrophobic interaction occurred when these functional groups in the adsorbent approached the adsorbate with the same ring structure, which enhanced the adsorption selectivity towards flavonoids. The hydrophobic interaction played an important role in the selective adsorption. Atomic force microscopy provided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This inferred that the quercetin has been grafted onto cross-linked chitosan. Zhang et al (2013) also reported the presence of quercetin by FTIR analysis.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 92%
See 1 more Smart Citation
“…This inferred that the quercetin has been grafted onto cross-linked chitosan. Zhang et al (2013) also reported the presence of quercetin by FTIR analysis.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 92%
“…A known quantity of QICR was packed in the glass column and the pressure was applied from the top of the column. Quercetin solution at pH‐4 was loaded into the column and the concentration of quercetin was measured in the collected fraction (Zhang et al., 2013). The adsorption capacity was calculated using Equation (5).…”
Section: Methodsmentioning
confidence: 99%